STUDENTS DROP-OUT IN INSTITUTIONS OF HIGHER LEARNING IN ETHIOPIA MAGNITUDE CAUSES AND CURES - Asmerom, Kidane; Lakew, Wolde Tekle; Makonnen, Yimer; Yusuf, Orner Abdi (The Ethiopian Journal of Education, 2024)
This study attempted to estimate the number of dropouts in the higher institutions of learning in the nation as a whole and whether there was a regional variation in this regard by taking into consideration faculties and subjects with emphasis on English and Mathematics. Many factors were used to determine the causes for the sampled dropout. Among other things, it was concluded that many of the sampled student discontinued their education for academic reasons and a few for non-academic ones as revealed both by empirical observations and correlational analyses. These were then followed by a number of suggestions to alleviate the prevailing high attrition rate.